Community Political Participation in Kuantan Singingi Regency Head General Election During the 2020 Covid-19 Pandemic Era - Sudaryanto Sudaryanto; Ruslyhardy Ruslyhardy; Iwan Arasit (JOELS: Journal of Election and Leadership, 2022)
In Indonesia, one of the regencies/cities that have carried out the Regional Head Election is Kuantan Singingi Regency, which was on September 9, 2020, but the number of voters has decreased. This problem is related to health, economy and human resources. Public political participation in general can be categorized in several forms, namely; election activities, trying to influence, organizational activities, seeking connections and acts of violence. This research is qualitative using descriptive analysis approach. Research informants are the Chair of the General Election Commission, the Chair of the Election Oversight Body, academics, election activists and community leaders. As a result, voter participation has decreased due to the lack of optimal election education activities and concerns about the spread of the corona virus.